Retrospective Study: Serum Hemoglobin, Erythrocyte, and Creatinine Profiles in Chronic Kidney Disease Patients Following Hemodialysis - Purnadianti, Mely; Muhtadi, Selviani (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Chronic kidney disease (CKD) is a progressive and irreversible pathological condition with multiple etiologies, leading to a gradual decline in kidney function. Hemodialysis is employed to eliminate metabolic waste products and specific toxins. This study aimed to evaluate the correlation between hemoglobin levels, erythrocyte count, and serum creatinine levels in CKD patients after undergoing hemodialysis therapy. A cross-sectional study with an analytical observational design was conducted on 25 patients selected through purposive sampling. Data were analyzed using Pearson’s correlation test. The analysis revealed a strong positive correlation between hemoglobin levels and erythrocyte count (correlation coefficient r = 0.932; p < 0.001), indicating a statistically significant association. However, no significant correlation was observed between hemoglobin and creatinine levels (r = 0.099; p = 0.636), nor between erythrocyte count and creatinine levels. In conclusion, this study found a significant association between hemoglobin levels and erythrocyte count in CKD patients post-hemodialysis at Gambiran Hospital. However, no significant relationship was observed between hemoglobin or erythrocyte parameters and serum creatinine levels.